Very Long Chain Polyunsaturated Fatty Acids Accumulated in Triacylglycerol Are Channeled From Phosphatidylcholine in Thraustochytrium - Zhao, Xianming; Qiu, Xiao (Frontiers in Microbiology, 2019)
Thraustochytrium is a marine protist that can accumulate a large amount of very long chain polyunsaturated fatty acids (VLCPUFA) in triacylglycerols (TAG). How these freshly synthesized VLCPUFAs are channeled into TAG remains unknown. In this study, the glycerolipid profile of Thraustochytrium at log and stationary growth stages was first analyzed by lipidomic tools, and then 14C-acetate and 14C-glycerol were used to trace the flux of fatty acids and backbone in glycerolipids. Lipidomic analysis showed that VLCPUFAs were mostly allocated to phosphatidylcholine (PC) and TAG. PC possessed a relatively stable profile of VLCPUFAs, whereas TAG carrying VLCPUFAs were significantly increased at the stationary phase. 14C-acetate labeled VLCPUFAs were predominately incorporated into PC initially but were mostly found in TAG at later time of labeling. Positional analysis showed that PC had either one VLCPUFA at its sn-2 position (PC1) or two VLCPUFAs (PC2), while TAG incorporated VLCPUFAs almost exclusively at the sn-2 position. Similarly, 14C-glycerol was more efficiently incorporated into PC1 than TAG initially but was mostly found in TAG at later time of labeling, and diacylglycerol and PC1 shared a similar incorporation pattern. These results indicate that VLCPUFAs in TAG are mainly channeled from PC likely through diacylglycerol as the intermediate.